(untitled) (Journal of Artificial Intelligence & Research, 2024)
The evolution of blockchain technology has highlighted the need for innovative solutions to enhance the efficiency and security of consensus mechanisms. Traditional consensus algorithms, such as Proof of Work (PoW) and Proof of Stake (PoS), while effective in maintaining network integrity, often lead to substantial energy consumption and potential security vulnerabilities. This paper proposes novel artificial intelligence (AI)-based algorithms designed to optimize consensus mechanisms within blockchain networks, focusing on reducing energy consumption and enhancing security. By employing AI techniques, such as machine learning and predictive analytics, the proposed algorithms dynamically adapt to changing network conditions, improving overall efficiency. This research underscores the critical role AI plays in transforming consensus mechanisms, paving the way for more sustainable and secure decentralized networks.